PEMANFAATAN KARBON AKTIF UNTUK MEREDUKSI BAHAYA MERKURI DAN SIANIDA PADA PERTAMBANGAN EMAS RAKYAT - Imelda Hutabarat (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2022)
Small scale gold mining uses a lot of mercury and cyanide reagents in gold processing without sufficient knowledge and skills in its mineral processing and waste management. As a result, the processing of small scale gold mining becomes an environmental impact in the community because it is still carried out traditionally by ignoring environmental and health impacts, including the selection of inappropriate technology. Therefore, the community needs to be given education and appropriate technology related to process waste management, so that the process carried out is more effective, efficient and reduces the impact on the environment. This activity is a ccommunity service (Pengabdian kepada Masyarakat) activity, Bandung Polytechnic on Energy and Mining (PEP Bandung) with the theme of Utilization of Adsorbents of Zeolite and Activated Carbon to Reduce Industrial Waste (a case study of gold processing waste treatment in Sukabumi Regency) with the aim that the community around gold processing locations can consciously and independently manage gold processing waste so that: first, the impact on humans and the environment can be minimized and secondly, the use of process water can be reused effectively and efficiently. The method used is to test the absorption of metals dissolved in cyanide solution and see the percentage of dissolved metal absorption in activated carbon. The results obtained are that activated carbon is able to absorb metals especially mercury (Hg), gold (Au), copper (Cu), lead (Pb), zinc (Zn) and arsenic (As). As part of the social activity to the community, it has been prepared simple equipment to absorb metal dissolved in a cyanide solution that can be utilized in a waste pond of mining gold processing community in Simpenan District, Sukabumi Regency.